Behavioral Contract Theory - Kőszegi, Botond (Journal of Economic Literature, 2014)
This review provides a critical survey of psychology-and-economics (“behavioral-economics”) research in contract theory. First, I introduce the theories of individual decision making most frequently used in behavioral contract theory, and formally illustrate some of their implications in contracting settings. Second, I provide a more comprehensive (but informal) survey of the psychology-and-economics work on classical contract-theoretic topics: moral hazard, screening, mechanism design, and incomplete contracts. I also summarize research on a new topic spawned by psychology and economics, exploitative contracting, that studies contracts designed primarily to take advantage of agent mistakes. (JEL A12, D03, D82, D86)